Feasibility Analysis of Wheelchair Production Based on Engineering Economics - Fitriansyah, Aidil; Makmuri, M Kumroni (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2025)
This study aims to analyze the feasibility of wheelchair production based on engineering economics to determine whether the project is technically and economically viable. The research employed both primary and secondary data. Primary data were collected through questionnaires distributed to 100 respondents to identify user preferences, purchasing power, and perceptions of locally produced wheelchairs, while secondary data were obtained from statistical reports, market studies, and government regulations. The analysis applied investment appraisal methods including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Break Even Point (BEP). The results indicate that the total initial investment required is Rp 12,000,000 with monthly operating costs of Rp 30,925,000. The projected monthly revenue reaches Rp 75,000,000, generating an average net profit of Rp 44,075,000. The NPV of Rp 106,633,167 and IRR of 28.68% show that the project is highly profitable, with a payback period of 1 year and 1 month, and a BEP of 14.9 units. These findings conclude that wheelchair production is financially feasible and has strong market potential, provided that cost management, marketing strategy, and risk mitigation are well implemented.